PEMANFAATAN ANALISIS SEMIOTIKA ROLAND BARTHES TERHADAP NILAI-NILAI AKHLAK KARIMAH DALAM FILM ANIMASI - Syahid Nabaul Azim; Ahmad Asrof Fitri, Muhammad N. Abdurrazaq (JOURNAL OF COMMUNITY DEDICATION, 2022)
This study aims to find out what are the moral values of Karimah and what are the dominant moral values of the animated film Adit and Sopo Jarwo episode 76 on MNC TV. The researcher used Roland Barthes style semiotic analysis method to answer the research problem formulation. The purpose of this technique is to find out the meaning of the moral values represented by a sign in a film and then conveyed to the general public. This study uses a qualitative approach that understands the meaning and signs found in the animated film Adit and Sopo Jarwo. The results of this study can be concluded that in the animated film Adit and Sopo Jarwo episode 76 on MNC TV there are moral values, namely first, good morals to Allah SWT by worshiping and always being grateful to Allah SWT. Second, good morals towards fellow human beings by helping each other, giving good advice, respecting both parents, and giving love to their children. And the most dominant moral values are moral values towards fellow human beings.